Strategi Pengembangan Materi Pendidikan Agama Islam - Devi Elsi Susanti; Asmaiwaty Arief; Rehani Rehani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid development of Islamic religious education, both in the curriculum and in learning, has encouraged educational institutions, educators (teachers or lecturers) to be able to innovate in PAI learning. Developing appropriate learning strategies in Islamic religious education is not only related to teaching methods, but also involves the use of appropriate learning media, utilization of existing resources, and the creation of a conducive learning environment. By developing appropriate learning strategies, it is hoped that the goals of Islamic education, both in understanding religious teachings and in forming noble morals, can be achieved optimally. This research aims to determine strategies for developing Islamic religious education materials. This research uses library research with references from books, articles and analysis of existing problems. The results of this research are to find out what strategies are used in developing Islamic religious education materials.